(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
It has been substantiated that Reactive Power Injections (RPI) at optimal locations reduce power losses (PLS & QLS) and enrichment in node voltage profile, thereby enhancing efficacy. Most researchers considered the reduction in real power loss (PLS) and capacitor purchase costs as objectives to get Financial Savings (FS). However, this work focuses on maximizing FS by optimal allocation and capacity determination of capacitors in Electric Power Distribution Systems (EPDS), considering the reduction in power losses and capacitor purchase and its associated costs as objective subject to satisfaction of equality and inequality constraints. Cheetah Optimizer (CO) has been considered to solve the Financial Based Objective Function (FBOF) to obtain an improved solution in this work. Researchers normally adopt a Sensitivity Based Index (SBI) to identify potential node RPIs by ranking. Nevertheless, the CO technique will do both optimal placement and sizing of capacitors. The efficacy of the projected CO has been validated using three real EPDS. The outcomes of CO have been compared with other optimization techniques available in the literature. Simulated results reveal that CO effectively minimizes power losses with considerable improvement in FS compared to other techniques.